Luteimonas gilva sp. nov., isolated from farmland soil. Issue 5 (5th May 2020) - Xiong, Luo; An, Lijin; Zong, Yuanyuan; Wang, Mengjie; Wang, Gejiao; Li, Mingshun
Abstract : A Gram-stain-negative, rod-shaped bacterium, strain H23 T, was isolated from farmland soil sampled in Enshi City, Hubei Province, PR China. The isolate grew optimally at 28–32 °C, pH 8.0 and with 0.5 % (w/v) NaCl. Based on the results of 16S rRNA gene sequence and phylogenetic analyses, strain H23 T belonged to the genus Luteimonas with the highest degree of 16S rRNA gene sequence similarity to Luteimonas cucumeris Y4 T (97.41 %). The DNA G+C content was 65.88 mol%. The average nucleotide identity and the Genome-to-Genome Distance Calculator results also showed low relatedness (below 95 and 70 %, respectively) between strain H23 T and type strains in the genus Luteimonas . Ubiquinone-8 was the predominant quinone. The major fatty acids were iso-C15 : 0, iso-C16 : 0, iso-C17 : 0 and iso-C17 : 1  ω9 c . Polar lipids were dominated by diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and unidentified phospholipids. Low digital DNA–DNA hybridization values, as well as physiological and biochemical differences, such as no casein hydrolysis, being catalase-negative, and tesing positive for cystine arylamidase, α-chymotrypsin and N -acetyl-β-glucosaminidase, could distinguish strain H23 T from its closely related species. Strain H23 T is considered to represent a novel species in the genus Luteimonas, for which the name Luteimonas gilva sp. nov. is proposed, with strain H23 T (=CCTCC AB 2019255 T =KCTC 72593 T ) as the type strain.